KOMUNIKASI ORGANISASI VERTIKAL SEBAGAI PEMODERASI PENGARUH KUALITAS SUMBER DAYA MANUSIA, BUDAYA ORGANISASI DAN TEKNOLOGI INFORMASI PADA PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL (Studi Kasus Pada Badan Keuangan dan Aset Daerah Kabupaten Kul - Sri Ayem; Nur Fina Saputri (Jurnal Akuntansi, 2018)
This study aims to determine the effect of human resource quality, organizational culture and information technology on the application of accrual-based SAP with vertical organizational communication as a moderation variable. This research was conducted at BKAD Kulonprogo Regency. The respondents consist of 40 BKAD staff using simple random sampling method. The data used in the form of primary data by using questionnaires from some modified previous research, interviews, and observations. Moderation analysis with moderated regression analysis (MRA) test was used to analyze the data. The results of this study indicate that the quality of human resources positively affect the application of accrual-based SAP, organizational culture has a positive effect on the accrual-based SAP applications, information technology has no effect on the accrual-based SAP implementation, vertical organizational communication strengthens the relationship between the quality of human resources with the accrual-based SAP implementation, vertical organization does not reinforce the relationship between with the accrual-based SAP implementation, and vertical organizational communication does not reinforce the relationship between information technology and the accrual-based SAP implementation.Keywords: Accrual-Based SAP Application, Information TechnologyOrganizational Culture, Vertical Organization Communication, Quality of Human Resources